Menggali Nilai-Nilai Perkawinan Masyarakat Adat Wodonwair Ditinjau dari Aspek Sosial Budaya di Desa Wolomotong Kecamatan Doreng - Petrus Ferdinandez; Abdullah Muis Kasim; Danar Aswim (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the values in indigenous marriages in the Wodonwair Society, Wolomotong Village and how the application of customary marriage by the Wodonwair community is on review of the socio-cultural aspect. The research uses qualitative research. The data sources used in this study are primary data sources and secondary data sources. The data analysis technical used consists of data reduction, data presentation, and drawing conclusions. The traditional marriage in Wolomotong Village people is recognized by the local community and run from every layer of local people or from generation to generation. In the customary marriage process that exists in the people of Wolomotong Village have the stages that must be carried out by a couple who want to commit indigenous marriage. Each stage in the marriage process has its own value. Traditional marriage is still being run by all communities present in the Wodonwair Village area.